Analysis of school support: Systematic literature review of core Chinese- and English-language journals published in 2000–2021 - Li, Jun; Hu, Ziao; Pan, Ling (Frontiers in Psychology, 2022)
School support is of great significance to students’ academic quality and overall physical and psychological development. However, there is still ambiguity in the English and Chinese studies on the concept and measurement tools of school support. The data for this study were sourced from the literature on school support included in the China National Knowledge Network (CNKI) and Web of Science (WOS) from 2000 to 2021. A systematic literature review was conducted through literature inclusion and data extraction according to the PRISMA guidelines. Finally, 36 core-journal articles with high academic reference value and authority are identified, including 7 in Chinese and 29 in English. The following research results were obtained: (1) Related research in both Chinese and English showed an overall increasing trend. (2) The concepts and measurement tools of school support were not clear, and most studies used concepts and measurement tools of “social support” or “school climate” as substitutes of school support. (3) Most of the previous studies were based on social support theory, ecological system theory, and school climate theory. (4) The research mainly adopts quantitative research methods and focuses on special student populations or students below the high school level. Overall, previous studies indicated that school support has a positive impact on student development. Therefore, future research should be broadly extended to the knowledge system in higher education. On the basis of clarifying the concept of school support, it is necessary to try to develop and validate school support measurement tools with great reliability, validity and general applicability to provide practical reference for educators around the world.